Viabilitas Biofungisida Produk Lokal dan Aplikasinya untuk Penundaan Gejala Penyakit Hawar Daun Tanaman Kentang - Naufal, Mochammad Fa’iq Qoys; Purwantisari, Susiana (Bioma : Berkala Ilmiah Biologi, 2020)
Late blight disease caused by Phytophthora infestans, is probably the single most important disease of potatoes worldwide. Infected plants were quickly killed and were difficult for replanting, causing significant losses for the growers. Various control methods were examined including the use of biocontrol agents of Trichoderma agent.  The research objective was to determine the ability of biofungicide product from Temanggung local farmer group to delay late blight disease incidence on potato plants in the field. The in vivo experiment was carried out at potato land area located at Kaponan  Sub District, Pakis District and Magelang Regency. Complete Randomized Design  with six treatments and twenty replication was applied and each of which was placed in a different plot. On the first plot treatment was given chemical fertilizer application (P0);The second plot treatment  (P2) was given with leaking and spraying application of biofungicide ( H-7, H+8, and H+15); The third plot treatment (P3) was given with spraying application of biofungicide   (H+8, H+15, and H+21); The fourth plot treatment (P4) was given with spraying application of biofungicide   (H+8, H+15, H+21 and H+28), and the last tretment (P5) was given with no application of chemical fungiside and pesticide. Result of the research showed that application of biofungicide could delay late blight disease incubation period until 14 days compared the control treatment (P0). The percentage of viability of the active biofungicide after being stored for 4 months still shows a high value of 87.13%, so that this local product biofungicide still meets the feasibility standard for its application in the field.